Empowering Sustainable Agriculture in Towua Village, Sulawesi Tenggara: Enhancing Efficiency through Organic Feed Production, Pond Management, and Business Training - Nuryadi, Ahmad Muhlis; Hamka, Eddy; Fajriani, Alfiah; Sulisworo, Dwi; Erviana, Vera Yuli; Maryani, Ika (The Indonesian Institute of Science and Technology Research, 2024)
The livelihood of the residents of Towua Village is generally farming, including both pond farming and rice field farming. Towua Village has a pond area of 585.69 hectares used for milkfish farming. Discussions with the village head revealed that the productivity of the community-owned ponds is still very low because they are managed traditionally. This issue also affects the Harapan Jaya Bandeng Farmers Group. One possible solution is to implement or apply technology to help improve the quality of the ponds. The solutions to address the partner's problems include increasing the supply of natural feed through organic farming systems, improving pond management and governance, and providing business management training. These solutions are implemented using a holistic and multidisciplinary research-based approach to achieve farmers' welfare and village economic independence. The method used in this activity is the action research approach. The results of training, assistance, and monitoring of pond quality have led to an 80% increase in partner knowledge, an 80% increase in partner skills, a 60% increase in partner accessibility, and a 50% increase in partner income.